The Role of Terrestrial and Space Environments in Launch Vehicle Development - Johnson,Dale L. (2019)
ABSTRACT: Natural (Terrestrial & Space) Environment (NE) phenomena play a significant role in the design and flight of aerospace vehicles and in the integrity of the associated aerospace systems and structures. Natural environmental design criteria guidelines described here are based on measurements and modeling of atmospheric and climatic phenomena relative to various aerospace vehicle development and mission/operational procedures, and for vehicle launch locations. Both the terrestrial environment (0-90 km altitude) and the space environment (Earth orbital altitudes) parameters and their engineering application philosophy are given with emphasis on launch vehicle-affected terrestrial environment elements. This paper also addresses the basis for the NE guidelines presented, the interpretation of the guidelines, and application to the development of launch or space vehicle design requirements. This paper represents the first of three on this subject.